SAFETY IN THE DIGITAL AGE: INVESTIGATING THE IMPACT OF ARTIFICIAL INTELLIGENCE AND EMERGING TECHNOLOGIES ON OCCUPATIONAL HEALTH AND SAFETY (Lex localis - Journal of Local Self-Government, 2025)
Background: The rapid integration of artificial intelligence (AI) and emerging technologies such as IoT, robotics, and wearable devices has transformed modern workplaces, offering significant advancements in productivity and safety. However, these innovations also introduce new challenges for occupational health and safety (OHS), including physical risks, psychological stress, ethical concerns, and training gaps. This study investigates the dual impact of these technologies on workplace safety, aiming to identify both benefits and emerging risks.Methods: A mixed-methods approach was employed, combining quantitative surveys (n = 150) and qualitative interviews (n = 20) with professionals from healthcare, manufacturing, logistics, and construction sectors. Data were analyzed using descriptive and inferential statistics for quantitative responses and thematic analysis for qualitative insights. The study focused on technology adoption levels, safety outcomes, psychological impacts, training adequacy, and ethical concerns.Results: Findings revealed that 60% of participants reported improved physical safety due to AI, yet 13.3% highlighted risks from automation errors. Nearly half (46.7%) experienced increased stress due to digital surveillance, and 60% cited inadequate training on new technologies. Ethical concerns, such as bias and privacy violations, were prominent, with 43.3% expressing high levels of concern.Conclusion: While AI and emerging technologies enhance workplace safety, they also pose significant psychological, ethical, and operational challenges. The study underscores the need for comprehensive training programs, robust ethical frameworks, and adaptive OHS policies to ensure safe and equitable integration of these technologies. Future efforts must prioritize human-centered design and cross-sector collaboration to address these evolving risks.